Flow field optimization for the solar parabolic trough receivers in direct steam generation systems by the variational principle. (November 2016) - Liu, Yun; Chen, Qun; Hu, Kang; Hao, Jun-Hong
Highlights: Optimize the fluid flow pattern in solar parabolic trough receivers. Applying the variational principle yields the optimization equations in theory. Solving the optimization equations gives the optimal flow fields directly. Longitudinal vortexes effectively reduce the circumferential temperature difference. The optimized flow patterns provide a guidance to design the receiver structures. Abstract: Direct steam generation (DSG) systems with parabolic trough solar receivers have higher operation temperature and lower investment than double-loop systems. However, they have not been widely employed in commercial plants due to some reasons including the unreliability of solar receivers. In this contribution, in order to improve the reliability, we apply the minimum circumferential temperature difference on the absorber of a solar parabolic trough receiver as the optimization objective, and set the continuity equation, the energy conservation equation and prescribed viscous dissipation rates as constrains to construct a Lagrange function. Then, the variational principle is used to derive the optimization equations that the optimal flow field should satisfy to minimize the circumferential temperature difference. Finally, the convective heat transfer processes in a typical receiver are optimized by the newly derived optimization equations to show the applications. The results show that generating longitudinal vortexes along the main flow in the receiver reduce the circumferential temperature difference effectively, e.g. from 69 K to 42 K (39% reduction), which provides a guidance for the structural optimization of practical receivers to improve the reliability.